Clinical counseling on sun protection and indoor tanning avoidance: a survey of current practices among U.S. health care providers - Holman, Dawn M. (Prev Med, 2019)
Clinicians can play a role in skin cancer prevention by counseling their patients on use of sun protection and indoor tanning avoidance. We used data from the 2016 DocStyles, a web-based survey of U.S. primary care providers, to examine skin cancer prevention counseling practices among 1,506 providers. In 2018, we conducted logistic regression analyses to examine factors associated with regularly providing counseling. Almost half (48.5%) of all providers reported regularly counseling on sun protection, and 27.4% reported regularly counseling on indoor tanning. Provider characteristics associated with regular counseling included having practiced medicine for ≥16 years (sun protection: adjusted prevalence ratio [aPR]=1.27, 95% confidence interval [CI]=1.15, 1.41; indoor tanning: aPR=1.38, 95% CI=1.17, 1.63), having treated sunburn in the past year (sun protection: aPR=1.78, 95% CI=1.46, 2.17; indoor tanning: aPR=2.42, 95% CI=1.73, 3.39), and awareness of US Preventive Services Task Force recommendations (sun protection: aPR=1.73, 95% CI=1.51, 2.00; indoor tanning: aPR=2.70, 95% CI=2.09, 3.48). Reporting barriers to counseling was associated with a lower likelihood of regularly counseling on sun protection (1-3 barriers: aPR=0.82, 95% CI=0.71, 0.94; 4+ barriers: aPR=0.80, 95% CI=0.69, 0.93) and indoor tanning (1-3 barriers: aPR=0.72, 95% CI=0.57, 0.91; 4+ barriers: aPR=0.61, 95% CI=0.47, 0.78). Barriers to counseling included lack of time (58.1%), more urgent health concerns (49.1%), and patient disinterest (46.3%). Although many providers report regularly counseling patients on skin cancer prevention, most report serious barriers to providing such counseling. Additional research could explore strategies to integrate compelling and informative skin cancer prevention counseling into current provider practices.